Anti-RAFLS Triterpenoids and Hepatoprotective Lignans From the Leaves of Tujia Ethnomedicine Kadsura heteroclita (Xuetong) - Wang, Mengyun; Jiang, Sai; Hussain, Nusrat; Zafar, Salman; Xie, Qingling; Huang, Feibing; Mao, Linxi; Li, Bin; Jian, Yuqing; Wang, Wei (Frontiers in Chemistry, 2022)
A pair of 3,4-seco-cycloartane triterpenoid isomers with a rare peroxy bridge, namely, xuetonins A and B (1 and 2), four new lignans xuetonlignans A–D (3–6), a new sesquiterpene xuetonpene (7), and a new natural product xuetonin C (8), along with 43 known compounds, were obtained from the leaves of Tujia ethnomedicine, Kadsura heteroclita. Their structures and configurations were determined with the help of a combination of 1D- and 2D-NMR, HRESIMS spectra, electronic circular dichroism (ECD), and X-ray diffraction data. Compounds 2, 10, 13–15, and 17–19 showed moderate-to-potent activity against rheumatoid arthritis fibroblast-like synoviocytes (RAFLS) with IC50 values of 19.81 ± 0.26, 12.73 ± 0.29, 5.70 ± 0.24, 9.25 ± 0.79, 5.66 ± 0.52, 11.91 ± 0.44, 13.22 ± 0.27, and 15.94 ± 0.36 μM, respectively. Furthermore, compounds 22, 25, and 31 exhibited significant hepatoprotective effects against N-acetyl-p-aminophenol (APAP)–induced toxicity in HepG2 cells at 10 μM, and the cell viability increased by 12.93, 25.23, and 13.91%, respectively, compared with that in the model group (cf. bicyclol, 12.60%).